A Holistic Approach to Carbon Trading Based on AI, Blockchain, and Satellite Data: A Study on East Java Protected Forest - Haryono, Haryono; Rahman, Arief; Zainal, Rifki Fahrial; Santoso, Bagus Teguh; Endarto, Budi (Westscience Press, 2025)
This study explores a holistic approach to carbon trading by integrating Artificial Intelligence (AI), blockchain technology, and Geographic Information Systems (GIS) to address challenges in managing East Java’s protected forests. AI models were utilized to estimate carbon stocks with high accuracy, while blockchain ensured transparent and secure carbon credit transactions. GIS analysis provided real-time monitoring of forest dynamics and identified high-priority zones for carbon trading. The integrated framework demonstrated significant improvements in efficiency, accuracy, and stakeholder trust compared to traditional methods. The study concludes that this approach is a scalable and effective solution for enhancing carbon trading systems and contributing to sustainable forest management in Indonesia.